An emerging role of mitochondrial quality control in bone metabolism: from molecular mechanisms to targeted therapeutic interventions - Ziqi Qin; Xiting Zhu; Yifei Shen; Huiling Ling; Ngaifung Ruan; Wushuang Ye; Yang Xu; Xueqi Gan (Cellular and Molecular Life Sciences)
Abstract The mitochondrial quality control system is the principal regulatory framework governing mitochondrial quantity, morphology, distribution, and functional integrity. This surveillance and regulatory machinery is essential for preserving cellular homeostasis and determining cellular differentiation. Mitochondria play a central role in maintaining the dynamic equilibrium between osteogenic differentiation and osteoclastic differentiation. Dysregulation of mitochondrial quality control can lead to disrupted mitochondrial homeostasis and functional impairments, disrupting the physiological processes of bone formation and bone resorption. However, comprehensive reviews elucidating the relationship between mitochondrial quality control and bone homeostasis are conspicuously lacking. This review systematically deconstructs the molecular architecture of mitochondrial quality control, elucidating the regulatory mechanism of each part (mitochondrial dynamics, mitophagy, mitochondrial biogenesis, mitochondrial redox) in bone-related cells. In addition, the mitochondrial quality control system in orchestrating cellular physiological activities is summarized to establish its indispensable in governing cellular homeostatic networks. Furthermore, the regulatory roles of the mitochondrial quality control system in bone-related cells and the balance between bone formation and resorption are reviewed. Finally, this review delineates the dysregulation of mitochondrial quality control in bone metabolic diseases and further advances mitochondrial quality control-targeted approaches for restoring mitochondria homeostasis, offering transformative strategies to treat bone metabolic diseases.